Energy-saving rectification technology with controlled mass exchange cycles between liquid and vapor - Bulii, Yurii; Kuts, Anatoly; Forsyuk, Andriy; Chumachenko, Sergii (My University, 2021)
Purpose of the article: the definition of the hydrodynamic mode of operation of barbotage perforated plates, of the efficiency of the technology of cyclic rectification in the mass-exchange columns equipped with barbotage perforated plates with variable free cross-sectionin and determining the consumption of heating steam in the rectificational and epyuratin columns. Research methods - analytical, chemical, physico-chemical with the use of instruments and research methods used in the production of rectified ethyl alcohol. Fluid consumption was controlled with the help of flowmeter RM, air velocity in the free section of the column - anemometer MS-13, in the holes of the plates - by calculation method. The concentration of volatile impurities of alcohol was determined on a gas chromatograph with a column HP FFAP 50 m × 0.32 m. Analysis of research samples was performed according to the State Standard of Ukraine 4222:2003 "Vodka, ethyl alcohol and water-alcohol solutions. Gas chromatographic method for determination of microcomponents content". An energy-saving technology of cyclic rectification with a continuous supply of heating steam and liquid to a mass-exchange column apparatus equipped with flake plates is proposed. The innovative method allows to prolong the time of contact of steam and liquid on plates up to 40-60 s and to reduce the time of overflow up to 1-1,7 s. In order to implement the technology, a rectification column design was proposed, equipped with flake plates with variable free cross-section.
Keywords: alcohol; plates; column; rectification; impurities; спирт; ректифікація; тарілки; колона; домішки; кафедра біотехнології продуктів бродіння і виноробства; кафедра інформаційних технологій, штучного інтелекту і кібербезпеки; кафедра теплоенергетики та холодильної техніки